Comparison of Maternal and Perinatal Outcome in Elective and Emergency Cesarean Section in a Tertiary Care Centre - Subedi, Anjali; Shrestha, Junu; Adhikari, Krishna Murari; Shrestha, Aashika; Gurung, Sangeeta (Birat Journal of Health Sciences, 2019)
Introduction: Cesarean delivery is the birth of a fetus via laparotomy and then hysterotomy. There are increased maternal and fetal morbidities and mortalities associated with such delivery, more in emergency cesarean section. Various studies have shown increasing trend of this mode of delivery worldwide leading to an increase in its associated risks and cost to the patients.Objective: The objective of the study was to compare the maternal and perinatal outcome in elective and emergency cesarean section.Methodology: It was a prospective comparative study conducted in the department of obstetrics and gynecology, Manipal Teaching Hospital from March, 2018 to September, 2018. All the patients undergoing cesarean section either elective or emergency were enrolled in the study after their consent. After collecting data from patients, maternal and perinatal outcomes were analyzed by using SPSS software.Results: There were total 1254 deliveries in the study duration, out of which 461(36.76%) were cesarean section (cs). The incidence of emergency cs was 86.5% and elective cs was 13.5%. Majority of women (75.7%) undergoing cs had no any antenatal visit. Around 81% of cases undergoing emergency cs were unbooked whereas only 48.4% of unbooked cases underwent elective cs (P-value 0.000). The most common indication for cs in both elective and emergency category was previous cs. There was no maternal complication in elective cs group but there were 8 cases (2%) in emergency cs (P value-0.293). In emergency cs group, 7 babies had poor Apgar score whereas all babies had good Apgar score in elective group (P-value-0.057). There was increased rate of NICU admission in emergency group than in elective group (3% vs 0%, P value-0.166).Conclusion The study showed that the incidence of cesarean section was high in our centre. The maternal and fetal risks were higher in emergency cs than in elective cs, but these were not statistically significant.